Analisis Pengaruh Return on Assets, Capital Adequacy Ratio dan Loan to Deposit Ratio terhadap Kebijakan Dividen pada Perbankan - Febriyanti, Sheilla; Melzatia, Shinta (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The study aims to: (1) Empirically test the impact of Return On Assets (ROA) on the dividend policy in BEI listed banking companies in 2018-2021 (2) Empirical test the influence of the Capital Adequacy Ratio (CAR) on dividend policies in the BEI listed Banking Companies in 2018-2020 (3) Empirically test the effect of the Loan to Deposit Ratios (LDR) on dividend policies in the BEI listed Banking Companies in 2018-2020. The population in this study are Banking company listed on the Indonesian Stock Exchange in 2022 which comprises 43 companies. Sampling using purposive sampling method and based on the defined criteria were obtained samples of as many as 12 companies. The analytical method used is multiple linear regression analysis Eviews version 10. The results showed that Return on Assets (ROA) has a negative effect on the dividend policy, Loan to Deposit Ratio (LDR) has a positive effect on the dividend policy, while the Capital Adequancy Ratio(CAR) has no effect over the dividend Policy. Keywords: Dividend Policy, Capital Adequacy Ratio, Loan To Deposit Ratio, Return On Assets.